The efficacy of the law and regulatory mechanisms in combating counterfeit drugs in Tanzania - Phoibe, Clifford Magili (Mzumbe University, 2024)
A dissertation submitted in partial fulfillment of the requirements for award of the degree of Master of Law (LLM) of Mzumbe University